(3fXQjI GdeQGLYI hBdjGJ GdJWHjb (B/s - (3GdUHGf, eMeO SejQs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI ddWHGYI(B, s, 2001)
(3aj gPG GdcJGH (B: 1- (3eYGjjQ GdeQGLYIGdeJYGQa YdjgG (B2- (3eSDhdjI GdeQGLY hCOGH GdSdhc Gdegfj (B3- (3JbQjQ GdeQGLY hGdSdhc Gdegfj (B4- (3JbQjQ GdeQGLY GdNGQLj (B5- (3GdQbGHI GdOGNdjI (B6- (3GdLhfH GdSdhcjI ddQbGHI GdOGNdjI (B7- (3bQGFf hCOdI GdEKHGJ aj GdeQGLYI (B8- (3GdeONd GdEMUGFj aj eLGd GNJHGQGJ GdeQGLY GdGOGQjI (B9- (3GdeQGLYI GdELJeGYjI hGNJHGQGJ GdJMbb ef GdCOGA GdELJeGYj ddhMOI GdEbJUGOjI (B10- (3GNJHGQGJ GdeQGLYI GdeSJfOjI (B11- (3GNJHGQGJ GdJMbb ef GdCUhd hGdNUhe hYfGUQ fJjLI GdCYeGds
Keywords: (3BdjGJ GdJWHjbs; (3fXQjI GdeQGLYIs